Compliance trabalhista e cultura organizacional: analisando a efetividade dos canais de denúncia no enfrentamento ao assédio moral - Lavor, Pâmela Vieira (Brasil, 2025)
This study analyzes the effectiveness of employment compliance programs, with a focus on whistleblowing channels, and examines their relationship to organizational culture and the role of human resources professionals in combating workplace bullying. The goal of the research was to understand how these programs, particularly whistleblowing channels, can be evaluated and improved in terms of their effectiveness and impact on promoting an ethical culture. To achieve this goal, a qualitative study was conducted using a case study, semi-structured interviews with 15 participants (employees and managers), and content analysis of the data collected. The results showed that while whistleblowing channels are widely recognized as necessary initiatives, they face significant challenges, such as lack of trust in confidentiality, fear of retaliation, and communication failures throughout the process, from registering the complaint to providing feedback. In addition, the study highlights the strategic role of human resources professionals in implementing and managing these programs, and the need to foster an organizational culture aligned with ethics and compliance values. Finally, the study suggests improvements, such as promoting a culture of whistleblowing and implementing follow-up programs for victims of harassment, with the goal of building employee trust and confidence.